Deglacial Land-Ocean Linkages at the Alaskan Continental Margin in the Bering Sea - Wang, Rong; Kuhn, Gerhard; Gong, Xun; Biskaborn, Boris K.; Gersonde, Rainer; Lembke-Jene, Lester; Lohmann, Gerrit; Tiedemann, Ralf; Diekmann, Bernhard (Frontiers in Earth Science, 2021)
A marine sediment record from the central Bering Sea, spanning the last 20 thousand years (ka), was studied to unravel the depositional history with regard to terrigenous sediment supply and biogenic sedimentation. Methodic approaches comprised the inference of accumulation rates of siliciclastic and biogenic components, grain-size analysis, and (clay) mineralogy, as well as paleoclimatic modelling. Changes in the depositional history provides insight into land-ocean linkages of paleoenvironmental changes. During the finale of the Last Glacial Maximum, the depositional environment was characterized by hemipelagic background sedimentation. A marked change in the terrigenous sediment provenance during the late Heinrich 1 Stadial (15.7 – 14.5 ka), indicated by increases in kaolinite and a high glaciofluvial influx of clay, gives evidence of the deglaciation of the Brooks Range in the hinterland of Alaska. This meltwater pulse also stimulated the postglacial onset of biological productivity. Glacial melt implies regional climate warming during a time of widespread cooling on the northern hemisphere. Our simulation experiment with a coupled climate model suggests atmospheric teleconnections to the North Atlantic, with impacts on the dynamics of the Aleutian Low system that gave rise to warmer winters and an early onset of spring during that time. The late deglacial period between 14.5 and 11.0 ka was characterized by enhanced fluvial runoff and biological productivity in the course of climate amelioration, sea-level rise, seasonal sea-ice retreat, and permafrost thaw in the hinterland. The latter processes temporarily stalled during the Younger Dryas stadial (12.9-11.7 ka) and commenced again during the Preboreal (earliest Holocene), after 11.7 ka. High river runoff might have fertilized the Bering Sea and contributed to enhanced upper ocean stratification. Since 11.0 ka, advanced transgression has shifted the coast line and fluvial influence of the Yukon River away from the study site. The opening of the Bering Strait strengthened contour currents along the continental slope, leaving behind winnowed sand-rich sediments through the early to mid-Holocene, with non-deposition occurring since about 6.0 ka.